2009
DOI: 10.1590/s1415-43662009000200016
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da amônia emitida de camas sobrepostas e piso concretado utilizados na criação de suínos

Abstract: RESUMOA criação de suínos em camas sobrepostas surgiu como alternativa ao uso excessivo de água utilizada na atividade, mas veio, também, o problema da emissão de gases poluentes, principalmente a amônia. Objetivou-se, com este trabalho, avaliar a quantidade de amônia emitida pelas camas de maravalha, casca de arroz e pelo piso de concreto, comparandoa com os níveis aceitáveis para a produção de suínos criados em camas, entre dezembro de 2002 e abril de 2003, no município de Concórdia, SC; três edificações (12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 2 publications
(2 reference statements)
1
3
0
5
Order By: Relevance
“…These low values of NH 3 are consistent with those discussed by SILVEIRA et al (2009, in studies conducted in pig nursery with different types in southeastern Brazil, but also by PAULO et al (2008), analyzing the emission of ammonia in the southern region of Brazil, for different types of superimposed bed, which reported values of ammonia concentration below that are recommended by the NR-15 (1978) and ACGIH (2001). TOLON et al (2010) also reported low levels of NH 3 (mean 2.0 ppm) in pig breeding facilities.…”
Section: Results E Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These low values of NH 3 are consistent with those discussed by SILVEIRA et al (2009, in studies conducted in pig nursery with different types in southeastern Brazil, but also by PAULO et al (2008), analyzing the emission of ammonia in the southern region of Brazil, for different types of superimposed bed, which reported values of ammonia concentration below that are recommended by the NR-15 (1978) and ACGIH (2001). TOLON et al (2010) also reported low levels of NH 3 (mean 2.0 ppm) in pig breeding facilities.…”
Section: Results E Discussionsupporting
confidence: 89%
“…This concentration of NH 3 similar in the dry season (summer) and rainy (winter) is in disagreement with other work, such as SAMPAIO et al (2007b), citing higher levels of NH 3 in the winter, and this fact justifies the conditions of climate and management at this time of year, like the closing of facilities, which favors the formation of ammonia and, consequently, a higher concentration. However, PAULO et al (2008), reported that ammonia levels are higher in summer, and this increase is associated to the fact that the animals ingest a larger amount of water and the need for constant power, a scenario that also generates increased production of solid and liquid waste and, consequently, increased production of gas on the installations. This variation in the concentration of NH 3 is associated with the types of facilities, which in arid and semiarid regions are generally open to the management and mainly to climatic factors, which are different in each region.…”
Section: Results E Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, greater air quality control can probably improve productivity levels and present lower animal health risks (PANDORFI et al, 2012). Ammonia (NH3) is an important gas found in swine production facilities, which besides being an irritant to the respiratory system, also affects the health of animals and workers (PAULO et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Durante a produção de suínos, uma grande quantidade de produtos é gerada e pode ser prejudicial ao meio ambiente, aos animais e ao homem. Liberando energia, dió xido de carbono, e gases da cama, alimentos, máquinas e implementos utilizados na ração (Sampaio et al 2005;Paulo et al 2009;Silveira et al 2009).…”
Section: Introductionunclassified